A Bibliometric Analysis of the Interplay between Social Entrepreneurship and Agricultural Development (Journal of Informatics Education and Research, 2024)
The development of social enterprises is enhanced by creativity, knowledge, experience, skills, social welfare, and social values. Agricultural social enterprises play an important role in modern agriculture, providing innovative and sustainable solutions to help farmers improve productivity. The role of social enterprise is growing rapidly globally, as many economies recognize the enormous value of the sustainable solutions provided by these organizations to solve social problems. Social enterprises are also known as a catalyst for agricultural development. Agricultural development is essential for economies with growing populations, and many social enterprises are working to address farmer challenges with their innovative solutions. Therefore, research on social enterprises in the context of agricultural development is very important. Despite extensive research, we do not have any bibliometric analysis on this topic. This analysis is important for understanding how social enterprises support farmers across the agricultural value chain. This study aims to fill this gap, consolidate research, and establish the state of the art in the field. In total, 225 publications from the Scopus database, covering the period 2013-2023, were selected. Scopus paper is used for changed types of analysis including documents by year, source, country, etc. Other analysis tools such as VOS viewer version 1.6.15 are also used. The study revealed influential journals, productive and cited authors, top countries and universities, influential articles, and collaborative networks. This study contributes to the theoretical base by presenting the structure, characteristics, and research agenda of social entrepreneurship and agricultural development.